Innovative Applications of Nanomaterials in Healthcare and Environmental Sustainability - Nouman, Muhammad; Khan, Abdul Qadeer; Tahir, Sumayya; Jamal, Deena; Mahmood, Hafiz Fazal; Israr, Fareeha; Hassan Zeb,; Yaqoob, Muhammad; Shams, Faiza (Indus Journal of Bioscience Research, 2025)
Background: Nanotechnology has revolutionized healthcare and environmental sustainability through its ability to manipulate materials at the nanoscale. Its unique properties, including high surface reactivity and improved efficiency, have enabled novel applications in pollution control, diagnostics, and advanced material synthesis. Objective: This narrative review aimed to explore the innovative applications of nanomaterials in healthcare and environmental sustainability, emphasizing their potential benefits, limitations, and future directions. Methods: A systematic search was conducted in databases including PubMed, Scopus, and Web of Science using predefined keywords. Peer-reviewed studies published between 2010 and 2023 were selected based on relevance and methodological rigor. Data were synthesized narratively, focusing on key applications, efficacy, and associated challenges. Results: Nanomaterials demonstrated superior efficacy in water purification (85–92% pollutant removal), air filtration (95% particulate capture), and drug delivery (40–60% reduced systemic toxicity). Diagnostic sensitivity reached 90–95%, and tissue engineering applications showed a 2.5-fold increase in regeneration efficiency. However, scalability, cost, and environmental safety concerns limited broader adoption. Conclusion: Nanotechnology offers transformative solutions for healthcare and environmental challenges. Addressing scalability and safety concerns through interdisciplinary collaboration will be essential to fully realize its potential.